iPad mini for dummies - Baig, Edward C. (John Wiley & Sons, 2015)
This new edition of iPad mini For Dummies covers all the latest tips and tricks for getting an even bigger bang out of your iPad mini. Presented in full-color and written in the straightforward but fun language that has defined the For Dummies brand for more than twenty years, this friendly guide walks you through the multitouch interface, going online, getting connected, packing your iPad mini with apps, games, e-books, photos, music, and movies, synchronizing your data, texting with iMessage, working with Siri, importing pictures and launching slideshows, getting organized with Reminders, finding your way with Maps, working with the Calendar, protecting your information, accessorizing your iPad mini, and much more.